Neurogenin 3 mediates sex chromosome effects on the generation of sex differences in hypothalamic neuronal development - Scerbo, María J.; Freire-Regatillo, Alejandra; Cisternas, Carla D.; Brunotto, Mabel; Arevalo, Maria A.; Garcia-Segura, Luis M.; Cambiasso, María J. (Frontiers in Cellular Neuroscience, 2014)
The organizational action of testosterone during critical periods of development is the cause of numerous sex differences in the brain. However, sex differences in neuritogenesis have been detected in primary neuronal hypothalamic cultures prepared before the peak of testosterone production by fetal testis. In the present study we assessed the hypothesis of that cell-autonomous action of sex chromosomes can differentially regulate the expression of the neuritogenic gene neurogenin 3 (Ngn3) in male and female hypothalamic neurons, generating sex differences in neuronal development. Neuronal cultures were prepared from male and female E14 mouse hypothalami, before the fetal peak of testosterone. Female neurons showed enhanced neuritogenesis and higher expression of Ngn3 than male neurons. The silencing of Ngn3 abolished sex differences in neuritogenesis, decreasing the differentiation of female neurons. The sex difference in Ngn3 expression was determined by sex chromosomes, as demonstrated using the four core genotypes mouse model, in which a spontaneous deletion of the testis-determining gene Sry from the Y chromosome was combined with the insertion of the Sry gene onto an autosome. In addition, the expression of Ngn3, which is also known to mediate the neuritogenic actions of estradiol, was increased in the cultures treated with the hormone, but only in those from male embryos. Furthermore, the hormone reversed the sex differences in neuritogenesis promoting the differentiation of male neurons. These findings indicate that Ngn3 mediates both cell-autonomous actions of sex chromosomes and hormonal effects on neuritogenesis.